Inhibition of Noroviruses by Piperazine Derivatives - Dou, Dengfeng (2011)
There is currently an unmet need for the development of small-molecule therapeutics for norovirus infection. The piperazine scaffold, a privileged structure embodied in many pharmacological agents, was used to synthesize an array of structurally-diverse derivatives which were screened for anti-norovius activity in a cell-based replicon system. The studies described herein demonstrate for the first time that functionalized piperazine derivatives possess anti-norovirus activity. Furthermore, these studies have led to the identification of two promising compounds (6a, 9l) that can be used as a launching pad for the optimization of potency, cytotoxicity, and drug-like characteristics.